Poetry as An Alternative to Teach Literature for EFL Students in English Course - As Sholihin, Ahmad Arif Burhanuddin; Adzani, Adam; Salam, Akmalus; Rohmana, Wahyu Indah Mala (Institut Agama Islam Negeri (IAIN) Kediri, 2023)
The purpose of the study is to investigate how effectively poetry works as an alternative teaching strategy for literature to English as a foreign language (EFL) Students. Poetry is a form of verbal art that evokes feelings, reflects thoughts, and conveys human experiences in a beautiful and creative way. This study explores the connection between teaching methods and literary works, with a specific focus on the use of poetry by teachers to improve language proficiency in EFL students. The study emphasizes a teacher's insights as a useful resource within the framework of an English course in Pare Kediri, East Java. The instructor highlights how well poetry works as an alternative teaching strategy for enhancing students' basic language proficiency, which includes speaking, listening, writing, and reading. The study also looks at the many advantages of including poetry in teaching languages. Using poetry as an alternative method to teach literature develops their critical thinking skills and language fluency in addition to their language ability. Moreover, it fosters a greater awareness and respect of one's cultural history and raises learning motivation. The research highlights the educational advantages of adding poetry into the curriculum and highlights the possibility of poetry as an alternative teaching method for EFL students. It is a promising option for instructors looking for cutting-edge and effective teaching methods because of its effectiveness. In the end, this study's conclusions support the inclusion of poetry in the curriculum as an alternative method to improve EFL students' language learning opportunities.